The ALA, public libraries and the Great Depression - Luyt, Brendan (2012)
During the Great Depression of the 1930s, the American Library Association (ALA) became active in an alliance of public administrators, bank executives and teachers defending public spending from powerful populist anti-tax coalitions seeking drastic tax cuts as a solution to economic stagnation. Librarians were encouraged by the ALA to join the fight for ‘constructive economy’ that would reform and strengthen the role of public institutions. On the surface, this appears to be another example of the cyclical calls for library action that Michael Harris identified as characteristic of the profession’s history. But in this case, the threat was real and the campaign produced significant longterm change. Librarians and their institutions became part of a much broader set of social forces that served to re-establish the hegemony of the American state at a time when it was particularly vulnerable to attack. In fact, the ALA’s calls for ‘constructive economy’ foreshadowed and made possible the post-war Fordist compromise between monopoly capital, the state and organized labour. This article examines the role the ALA hoped libraries would play in the campaign against the anti-taxation groups and, using the work of social theorists Antonio Gramsci and Nicos Poulantzas, situates these efforts within the wider political economy of the time.